Cross-Species Annotation of Expressed Genes and Detection of Different Functional Gene Modules Between 10 Cold- and 10 Hot-Propertied Chinese Herbal Medicines - Li, Arong; Li, Aqian; Deng, Zhijun; Guo, Jiewen; Wu, Hongkai (Frontiers in Genetics, 2020)
According to the Traditional Chinese medicine (TCM) system, Chinese herbal medicines (HMs) can be divided into four categories: hot, warm, cold and cool. Cool nature usually is categorized as cold nature, and warm nature is classified as hot nature. However, the detectable characteristics of gene expression profile associated with the cold and hot properties have not been studied. To address this question, a strategy for the cross-species annotation of conserved genes was established in the present study by using transcriptome data of 20 HMs with cold and hot properties. Functional enrichment analysis was performed on group-specific expressed genes inferred from the functional genome of the reference species (i.e., Arabidopsis). Results showed that metabolic pathways relevant to chrysoeriol, luteolin, paniculatin and wogonin were enriched for cold-specific genes, and pathways of inositol, heptadecane, lauric acid, octanoic acid, hexadecanoic acid and pentadecanoic acid were enriched for hot-specific genes. Six functional modules were identified in the HMs with the cold property: nucleotide biosynthetic process, peptidy-L-cysteine S-palmitoylation, lipid modification, base-excision repair, dipeptide transport, response to endoplasmic reticulum stress. While for the hot HMs, another six functional modules were identified: embryonic meristem development, embryonic pattern specification, axis specification, regulation of RNA polymerase Ⅱ transcriptional preinitiation complex assembly, mitochondrial RNA modification and cell redox homeostasis. The research provided a new insight into the HMs' cold and hot properties from the perspective of the gene expression profile of plants.